Desentralisasi dan Ketidakpastian Lingkungan sebagai Pemoderasi Pengaruh Sistem Akuntansi Manajemen Terhadap Kinerja Manajerial - Bawanti, Ida Ayu Gede Weda Satya; Krisnadewi, Komang Ayu (E-Jurnal Akuntansi; Vol 33 No 4 (2023), 2023)
The research aims to obtain empirical facts regarding the role of decentralization and uncertainty as a moderator of the relationship between the management accounting system (SAM) and managerial performance. The research location is at the BPD Bali sub-branch office. The method of determining the sample in this study was purposive sampling and obtained 74 heads of business and operational sections who were selected to be sampled with the criteria for a minimum of one year's position. Hypothesis testing uses MRA or moderated regression analysis. The results showed that management accounting systems (MAS) did not affect managerial performance, decentralization and environmental uncertainty acted as moderators and did not moderate the effect of MAS on managerial performance. Keywords: Managerial Performance; MAS; Decentralization; Environmental Uncertainty